The Role Of Cyberchondria In Mediating Health Anxiety, Fears And Obsessions Among Students Of Private Medical Colleges Sargodha - Usman , Muhammad; Afzal, Adnan; Afzal, Muhammad; Ahmad, Sundas; Habib, Bilal; Iqbal , Amina (Journal of Rawalpindi Medical College, 2025)
Objective: This study was conducted to examine the role of cyberchondria in mediating health anxiety, fears and obsessions among Students of private medical college. Methods: This descriptive correlational study was conducted at department of Psychiatry & behavioural sciences and Medical OPD of Rai Medical College, Sargodha. For this purpose data was collected from 150 medical students. The Cyberchondria Severity Scale (CSS‑12) was used to measure cyberchondria severity and Short Health Anxiety Inventory (SHAI) scale was used to measure Anxiety in patients. The Obsessive–Compulsive Inventory – Revised (OCI‑R) scale was used to measure Obsessive Compulsive Disorder (OCD) in patients. Results: Descriptive statistics (i.e. frequency distribution, percentages, mean, standard deviations, Pearson correlation and Anova) were the analytical methods to test the objectives. Results of correlational analysis showed positive but non- significant correlation between cyberchondria and mobile usage per day. Results of linear regression analysis indicate that cyberchondria has significant impact on health anxiety. Findings also indicate significant gender differences on health anxiety and cyberchondria, Females are more concerned about health and have more cyberchondria tendencies than males. However, non-significant difference on OCD patterns, mobile phone daily usage. Conclusion: This study shows that feeling constantly worried about your health and obsessively checking the internet for information can make you feel more anxious and stressed, and can also lower your quality of life. It also shows that cyberchondria has a great impact on health anxiety. Gender differences exist in health anxiety and cyberchondria. Keywords: Cyberchondria, Health Anxiety, Fear, OCD.